Radiation-synthesized metal-organic frameworks with ligand-induced Lewis pairs for selective CO2 Electroreduction - Liu, Wenhui (2025)
The electrochemical activation of inert CO2 molecules through C─C coupling reactions under ambient conditions remains a significant challenge but holds great promise for sustainable development and the reduction of CO2 emission. Lewis pairs can capture and react with CO2, offering a novel strategy for the electrosynthesis of high-value-added C2 products. Herein, an electron-beam irradiation strategy is presented for rapidly synthesizing a metal-organic framework (MOF) with well-defined Lewis pairs (i.e., Cu- Npyridinic). The synthesized MOFs exhibit a total C2 product faradic efficiency of 70.0% at -0.88 V versus RHE. In situ attenuated total reflection Fourier transform infrared and Raman spectra reveal that the electron-deficient Lewis acidic Cu sites and electron-rich Lewis basic pyridinic N sites in the ligand facilitate the targeted chemisorption, activation, and conversion of CO2 molecules. DFT calculations further elucidate the electronic interactions of key intermediates in the CO2 reduction reaction. The work not only advances Lewis pair-site MOFs as a new platform for CO2 electrochemical conversion, but also provides pioneering insights into the underlying mechanisms of electron-beam irradiated synthesis of advanced nanomaterials.